Evaluation of Anti-Nociceptive and Anti Diarrheal Activities of SaccharumOfficinarum Linn Fresh Juice on Albino Mice Model: Pharmaceutical Science-Pharmacology for Drug Discovery - Rohtash Singh (International Journal of Life Science and Pharma Research, 2022)
SaccharumOfficinarum L. (Sugarcane) is an indigenous medicinal plant of India mostly in Uttar Pradesh and Maharashtra. The fresh juice has been used traditionally as folk remedies for the treatment of many diseases including diarrhea, dysentery, and potent diuretics. The juice of the plant is used in menstruation cycle problems. It is also used as a tonic, anti-periodic etc. However, there was no study on whole plant juice of S. Officinarum Linn. The present study was designed to investigate the anti-nociceptive and anti-diarrheal activities of S. OfficinarumLinn on animal models at different doses such as 10 and 20 ml/kg. Various methods also were employed for investigating these activities such as castor-oil induced diarrhea, castor-oil induced entero pooling and gastrointestinal motility test, tail immersion, tail flick and hot plate methods. The diarrheal episode was inhibited by 31.88% and 40.95% for fresh juice at the doses of 10 and 20 ml/kg respectively. The juice significantly (p<0.05) reduced the intestinal volume (0.51 ± 0.04 ml) for 10 ml/kg and (0.46 ± 0.02 ml) for 20ml/kg) for fresh juice compared to control (0.63±0.02 ml) in castor-oil induced diarrhea and also decreased intestinal transit (54.58 – 60.12%) for fresh juice comparable with standard (loperamide 5 mg/kg). The fresh juice of S. officinarumL., increased latency in tail flick and tail immersion model and elevated the mean basal reaction time in hot plate model. The results of fresh juice of S. officinarumL. showed highly significant but dose dependent on anti-diarrheal and anti-nociceptive activities, which supports its use in traditional herbal medicine.